2018
DOI: 10.1002/etc.4058
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the usefulness of key green physicochemical properties: Quantitative structure–activity relationship for solvents from biomass

Abstract: In recent decades there has been a growing interest in the development of new solvents from biomass. Some of these new solvents have been classified as green because of their renewable and sustainable source. However, characterization from the ecotoxicological and physicochemical points of view is needed to categorize them as green solvents. We have selected several key physicochemical properties that can reflect environmental features (density, boiling point, critical aggregation concentration, and log p) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…ALs do not present potential health risks in terms of teratogenicity, maternal toxicity or systemic toxicity [4]. Biodegradability and ecotoxicological studies have also shown that they are environmental-friendly compounds with low ecotoxicity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…ALs do not present potential health risks in terms of teratogenicity, maternal toxicity or systemic toxicity [4]. Biodegradability and ecotoxicological studies have also shown that they are environmental-friendly compounds with low ecotoxicity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For that, previous studies have shown that the physicochemical properties of these solvents are suitable to consider them as green solvents. [18][19][20][21][22] The ecotoxicological effect of each of these solvents on different aquatic organisms and different levels of the food chain a (Allivibrio fischeri bacteria, Daphnia magna crustacean and Danio rerio fish embryos) has also been studied and reported. 2,[22][23][24][25][26][27] Overall, these studies showed that the ecotoxicity of these compounds is low; however, slight ecotoxicity was observed for butyl levulinate in A. fischeri bacteria, for furfural and 5-methylfurfural in D. magna and for ethyl and butyl levulinates, butyl lactate and furfural in D. rerio.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] The ecotoxicological effect of each of these solvents on different aquatic organisms and different levels of the food chain a (Allivibrio fischeri bacteria, Daphnia magna crustacean and Danio rerio fish embryos) has also been studied and reported. 2,[22][23][24][25][26][27] Overall, these studies showed that the ecotoxicity of these compounds is low; however, slight ecotoxicity was observed for butyl levulinate in A. fischeri bacteria, for furfural and 5-methylfurfural in D. magna and for ethyl and butyl levulinates, butyl lactate and furfural in D. rerio. Therefore, different levels of ecotoxicity have been found across the various tests used and among the different solvents studied, which may indicate that there are different mechanisms of toxicity depending on the organism.…”
Section: Introductionmentioning
confidence: 99%
“…in the pharmaceutical industry. 5 Some of these new solvents are biomass derivatives, 6 supercritical fluids, 7 ionic liquids (ILs) 8 and deep eutectic solvents (DES). 9 According to the principles of Green Chemistry, 10 solvents should present low vapour pressures and high boiling points, good recyclability, high solvating power, be environmentally and humanly safe and have renewable origin.…”
Section: Introductionmentioning
confidence: 99%